2015
DOI: 10.1149/2.0861602jes
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical, Microtopographical and Ambient Pressure X-Ray Photoelectron Spectroscopic Investigation of Si/TiO2/Ni/Electrolyte Interfaces

Abstract: The electrical and spectroscopic properties of the TiO 2 /Ni protection layer system, which enables stabilization of otherwise corroding photoanodes, have been investigated in contact with electrolyte solutions by scanning-probe microscopy, electrochemistry and in-situ ambient pressure X-ray photoelectron spectroscopy (AP-XPS). Specifically, the energy-band relations of the p + -Si/ALD-TiO 2 /Ni interface have been determined for a selected range of Ni thicknesses. AP-XPS measurements using tender X-rays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…1) was successfully created on a polycrystalline gold electrode by the ‘dip and pull' method39404142 (Supplementary Fig. 2) and characterized within the double-layer potential region ranging from −450 to +650 mV (versus Ag/AgCl/Cl − (sat.)…”
Section: Resultsmentioning
confidence: 99%
“…1) was successfully created on a polycrystalline gold electrode by the ‘dip and pull' method39404142 (Supplementary Fig. 2) and characterized within the double-layer potential region ranging from −450 to +650 mV (versus Ag/AgCl/Cl − (sat.)…”
Section: Resultsmentioning
confidence: 99%
“…p + -Si/TiO 2 as well as p + -Si/TiO 2 /Ni electrodes, with Ni thicknesses in the range of 0.5 to 10 nm, were contacted with 1.0 M KOH(aq) by use of the "dip and pull" method [18][19][20]. Operando APXPS data were collected while the electrode was under potential control between -1.4 V and +0.4 V vs Ag/AgCl.…”
Section: Methodsmentioning
confidence: 99%
“…We describe herein the use of operando ambient pressure X-ray photoelectron spectroscopy (APXPS) at the Advanced Light Source using tender X-rays in the 2 to 7 eV region to create photoelectrons that have sufficiently long inelastic mean-free paths (IMFP) to probe the semiconductor surface; the space charge region, the adjacent Helmholtz layer, and the bulk 3 electrolyte/water region [18][19][20]. Improving the activity of electrocatalysts composed of earthabundant elements, while achieving stability, is also of interest in the development of a stable, efficient solar-fuels generator.…”
Section: Introductionmentioning
confidence: 99%
“…A mass spectrometer collected and analyzed the 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 12 ejected secondary ions. The count rates of 30 Si, 48 Ti, 12 C + 133 Cs and 14 N + 133 Cs were collected as a function of sputtering cycle. SIMS data were collected for all TDMAT and TiCl 4 a-TiO 2 films.…”
Section: Secondary-ion Mass Spectroscopymentioning
confidence: 99%
“…The Si|TiO 2 |Ni|electrolyte interface has been probed via ambient pressure XPS. 17,48 It has been shown that for ultra-thin layers of Ni (< 1 nm) no conduction was observed in Fe(CN) 6 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 37 measurements using different excitation energies and varying the electron emission angle confirmed the presence of a metallic Ni phase below the surface. In addition, cross-sectional TEM and SEM images of the TiO 2 |Ni interface region further support the presence of metallic Ni at the interface of the TDMAT a-TiO 2 .…”
Section: Conduction Across A-tio 2 Interfaces With Varied Metal Comentioning
confidence: 99%